Arginase‐1+ bone marrow myeloid cells are reduced in myeloproliferative neoplasms and correlate with clinical phenotype, fibrosis, and molecular driver. (15th December 2022) - Bonometti, Arturo; Borsani, Oscar; Rumi, Elisa; Ferretti, Virginia Valeria; Dioli, Claudia; Lucato, Elena; Paulli, Marco; Boveri, Emanuela
Abstract: Introduction: Philadelphia‐negative myeloproliferative neoplasms (MPN) are clonal myeloid proliferative disorders characterized by sustained systemic inflammation. Despite its renowned importance, the knowledge concerning the inflammatory pathophysiology of these conditions is currently limited to studies on serum cytokines, while cellular immunity has rarely been investigated. Methods: In the present study, we targeted Arginase‐1 immunosuppressive myeloid cells in the bone marrow of MPN patients and healthy controls and investigated their clinical and prognostic significance. We demonstrated that MPN are characterized by a significant reduction of bone marrow immunosuppressive cells and that the number of these cells significantly correlates with several clinical and histopathological features of diagnostic and prognostic importance. Moreover, we identified an unreported correlation between a reduction of Arginase‐1+ bone marrow cells and the presence of CALR mutations, linking tumor‐promoting immunity and molecular drivers. Finally, we postulate that the reduction of bone marrow Arginase‐1+ immunosuppressive cells may be due to the migration of these cells to the spleen, where they may exert systemic immunomodulatory function. Conclusion: Altogether, this study preliminary investigated the contribution of cellular immunity in the pathogenesis of myeloproliferative neoplasms and identified a possible interesting therapeutic target as well as a set of new links that may contribute to unraveling the biological mechanisms behind these interesting hematological neoplasms.